Minimally Invasive Coronary Revascularisation Surgery: A Focused Review of the Available Literature. Issue 1 (2021) - Praet, Karel M Van; Kofler, Markus; Shafti, Timo Z Nazari; Al, Alaa Abd El; Kampen, Antonia van; Amabile, Andrea; Torregrossa, Gianluca; Kempfert, Jörg; Falk, Volkmar; Balkhy, Husam H; Jacobs, Stephan
No abstract available